Conditions of the Moon as Assessment Criteria: Turkish Moon Bases Competition Case - Sema Kirici; Pinar Dinc Kalayci (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
Sustainable human presence on the Moon is directly proportional to humanity's capacity to adapt to the Moon's environmental conditions. Designs on the lunar surface must be tailored to the physical conditions of the Moon. Within the scope of this study, a preliminary literature review identified atmosphere, pressure, wind, temperature, radiation, gravity, and dust as conditions that directly affect habitat design on the Moon, with each condition expressed as an evaluation criterion. As the sample area, five architectural design projects awarded in the Turkey Moon Bases National Idea Competition (Professional Category-2022) were analyzed. The main question of the study is to what extent these designs respond to the specified criteria. Based on the second literature review, which analyzed and clarified lunar conditions in depth, the projects were scored according to their compliance with the established criteria. Each project's site plan, plans, sections, 3D visuals, and project reports were evaluated on a scale of 100 points. In this context, a knowledge-based evaluation was conducted as an alternative to jury-based evaluation. Analyzing the projects from the Turkey Moon Base Competition is significant in providing a knowledge base for future studies in this field.